MODERN STUDENT VERSUS LEARNING ACTIVITY - LAŞCU, Lilia (Acta et Commentationes, Sciences of Education, 2019)
This article addresses the issue of the learning activity of modern students. In this context, the phenomenon of learning which has led to the elaboration of different conceptualizations of this is analyzed, being approached as an element of the educational process, product, activity and the mechanisms and stages specific to the learning activity are elucidated eloquently